Hemophagocytic Lymphohistiocytosis Associated with Salmonella typhi Infection in a Child: A Case Report with Review of Literature. (22nd November 2018) - Uribe-Londono, Juanita; Castano-Jaramillo, Lina Maria; Penagos-Tascon, Laura; Restrepo-Gouzy, Andrea; Escobar-Gonzalez, Andres-Felipe
Abstract : We present the case of an 8-year-old girl with hemophagocytic lymphohistiocytosis secondary to a Salmonella typhi infection. She received antibiotic treatment and intravenous immunoglobulin with complete resolution of the symptoms. We present a review of previously reported pediatric cases and propose a gradual approach to treatment.